Return of property and compesantion in Austria for those, who suffered from nazi regime - Schwarzinger, Michail (Genocidas ir rezistencija, 2002)
When Austria restored itself as an independent state at the end of the Second World War, measures were taken to compensate the Nazi victims. The term ‘restitution’ refers to the return of property owned by Nazi victims before 1938, while the term ‘compensation’ refers to measures to meet the basic needs of victims of the Nazi regime, such as benefits and pensions.
Keywords: Austria; German occupation; Holocaust; Jews; return of property